2015
DOI: 10.1002/elps.201400600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing and storage conditions on charged metabolomic profiles in blood

Abstract: The development of high-throughput metabolite measurement technologies has enabled the use of metabolomics for epidemiologic studies by profiling metabolite concentrations in large cohorts of human blood samples. Standard protocols are necessary to obtain unbiased profiles through multiple runs over long periods of time and to allow reliable statistical analyses. This study assessed the effects of sampling procedures and storage conditions on the stability of metabolomic profiles in plasma and serum. Charged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 20 publications
5
62
0
Order By: Relevance
“…This corresponds well to previous studies whereby ornithine, proline, and threonine (Davis et al 2009; Breier et al 2014), methionine (Breier et al 2014), pyroglutamic acid (Hirayama et al 2015) hexadecanoic acid (C16:0) stearic acid (C18:0) (Eijsden et al 2005; Breier et al 2014), urea (Heins et al 1995), uric acid (Holland et al 2005; Pinto et al 2014) as well as creatinine (Clark et al 2003) have been found in higher concentrations, while cysteine (Hirayama et al 2015) has been found in lower concentrations, in thawed blood samples. In the present study, metabolites involved in glycerol metabolism (glycerol, glycerol-3-phospahte and glyceric acid) were all observed in higher concentrations in the thawed plasma samples.…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds well to previous studies whereby ornithine, proline, and threonine (Davis et al 2009; Breier et al 2014), methionine (Breier et al 2014), pyroglutamic acid (Hirayama et al 2015) hexadecanoic acid (C16:0) stearic acid (C18:0) (Eijsden et al 2005; Breier et al 2014), urea (Heins et al 1995), uric acid (Holland et al 2005; Pinto et al 2014) as well as creatinine (Clark et al 2003) have been found in higher concentrations, while cysteine (Hirayama et al 2015) has been found in lower concentrations, in thawed blood samples. In the present study, metabolites involved in glycerol metabolism (glycerol, glycerol-3-phospahte and glyceric acid) were all observed in higher concentrations in the thawed plasma samples.…”
Section: Discussionsupporting
confidence: 92%
“…First, we used chloroform for metabolite extraction and organic solvents, such as lactate and glycerol, were educed from tube or filtration membrane [33]. Thus, these metabolites were not used for subsequent analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the proposed methodology is demonstrated in a comparative study of the metabolic profiles from baker's yeast ( S. cerevisiae ) samples. The development of high‐throughput CE‐MS metabolite measurement technologies has enabled the use of metabolomics by profiling metabolite concentrations in large cohorts of human blood samples . Effects of sampling procedures and storage conditions on the stability of charged metabolomic profiles in plasma and serum were studied.…”
Section: Analytical Applicationsmentioning
confidence: 99%